Comparisons of Cocaine-Only, Opioid-Only, and Users of Both Substances in the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). (15th April 2016) - Leeman, Robert F.; Sun, Qisi; Bogart, Devorah; Beseler, Cheryl L.; Sofuoglu, Mehmet
ABSTRACT: Background : Cocaine and opioid co-use is a notable public health concern, but little is known about correlates of this behavior. Most prior findings come from treatment samples and concern cocaine and heroin. Findings from a nationally representative sample involving primarily prescription opioid misuse would expand knowledge. Methods : Past-12-month cocaine and/or opioid users in Wave 1 of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) formed the sample ( N = 839). Cocaine-only, opioid-only, and cocaine/opioid co-users were compared regarding sociodemographics, other substance involvement, psychiatric, and medical conditions/events. Results : Opioid-only users were the largest group ( n = 622), followed by cocaine-only ( n = 144) and co-users ( n = 73). The vast majority of opioid misuse was of prescription opioids (1.4% with past-12-month use of heroin). Notably, co-users did not differ from single drug users in frequency of use of either drug. Co-users did not have significantly greater incidence of any psychiatric conditions, medial conditions, or events. In preliminary analyses, co-users were more likely than either single use group to report several classes of other drug use. However, for most comparisons, opioid use did not add substantial risk beyond cocaine use. Differences on multiple sociodemographic variables suggested opioid-only users were at lowest risk of negative outcomes. These results may relate to a finding that opioid-only users were less likely to have sought treatment. Conclusions/importance : This sample of past-12-month cocaine and/or opioid users had greater involvement with other substances, more psychiatric and medical conditions compared to the general population. Co-users had greater involvement with other substances than opioid-only users in particular.